A survey of quantitative methods in South African management - T. Wegner (South African Journal of Business Management, 1983)
Academics who are responsible for training South Africa's future pool of management resources need, as part of their management development programme, to emphasize the contribution of Quantitative Methods to management decision making. To give a complete appreciation of Quantitative Methods, practice of the subject in South African management. No current research in this direction exists. This research, undertaken through a mailed questionnaire to South African companies, aimed to establish the relative use of Quantitative techniques; their frequency of use, and their degree of success as useful information generators. This paper summarizes the result and draws tentative conclusions about the state of art in 1982 of Quantitative Methods in South African management as a decision support tool.
Keywords: 650